Association of Time-to-“Association of STONE Score Calculation To Reduced CT Scan Usage in the Emergency Department: A Systematic Review - Raynaldo Adnan Dinarwanto; Mochamad Sri Herlambang (International Medical Journal Corp. Ltd, 2026)
Introduction: The increasing use of computed tomography (CT) in emergency departments (EDs) for suspected renal colic raises concerns about radiation exposure and healthcare costs. The STONE clinical prediction score was developed to stratify patients by risk of urolithiasis, potentially guiding more judicious imaging. This systematic review aims to synthesize evidence on the association between STONE score implementation and CT scan utilization reduction in the ED. Methods: A systematic review was conducted following a structured screening protocol. Studies were included if they were conducted in an ED setting, involved adult patients with suspected kidney stones, implemented or evaluated the STONE score, and reported CT utilization outcomes. Data were extracted on study design, STONE score implementation, CT usage metrics, clinical outcomes, and implementation barriers. Results: Of 80 screened sources, only four studies directly examined STONE score implementation. The score demonstrated high heterogeneity in performance across studies but was useful for risk stratification (low-risk: 12% stone prevalence; high-risk: 83%). Direct evidence linking STONE score use to reduced CT ordering is scant. One prospective study showed STONE-guided reduced-dose CT protocols achieved 88.2% radiation dose reduction while maintaining high sensitivity. Broader evidence supports alternative strategies for CT reduction, including ultrasound-first protocols (achieving 7.7% absolute reduction) and low-dose CT protocols (75-88% dose reduction). Multispecialty consensus suggests 45% of clinical scenarios may require no imaging. Discussion: The STONE score’s primary utility appears to be identifying low-risk patients who may avoid imaging, rather than reducing overall CT ordering. Successful CT reduction requires multifaceted interventions beyond prediction tools, including ultrasound-first pathways, low-dose protocols, and system-level changes like interdisciplinary collaboration and workflow integration. Significant barriers persist, including clinician comfort, radiologist acceptance of reduced-dose CT, and a gap between evidence and practice. Conclusion: While the STONE score is a valid risk-stratification tool, direct evidence of its effectiveness in reducing CT scan utilization is limited. Its value is likely as part of a comprehensive, multi-strategy approach that includes ultrasound-first algorithms and dose optimization protocols. Future implementation research should focus on integrating the STONE score into clinical decision support systems within broader diagnostic pathways.